The Novel Protein Cj0371 Inhibits Chemotaxis of Campylobacter jejuni - Du, Xueqing; Kong, Ke; Tang, Hong; Tang, Haiyan; Jiao, Xinan; Huang, Jinlin (Frontiers in Microbiology, 2018)
cj0371 is a novel gene that is associated with Campylobacter jejuni virulence, and an isogenic mutant of cj0371 showed hyper chemotaxis and motility. Chemotactic motility is an important virulence factor and is involved in C. jejuni pathogenesis. Campylobacter sp. has specific variations of the common chemotaxis components, including histidine autokinase CheA, coupling scaffold protein CheV, chemotaxis response regulator protein CheY and several chemoreceptor proteins. In this study, we used immunoprecipitation combined with LC-MS/MS analyses to screen 6 chemotaxis pathway proteins that potentially interact with the putative protein Cj0371. qRT-PCR was used to quantitatively analyze the expression of these chemotaxis genes and basic flagella genes. The results showed that the expression of cheV, cj1110c, and cj0262c was significantly up-regulated, and 4 flagella genes also had up-regulated expression in the cj0371 mutant. GST pull-down analyses found that Cj0371 interacted with the receiver domain of the CheV protein. Enzyme-coupled spectrophotometric assays showed that the ATPase activity of CheA was higher when Cj0371 was not present in the chemotaxis reaction medium. Therefore, we concludes that cj0371 has a negative influence on C. jejuni chemotaxis, which may occur by adjusting the receiver domain of CheV to influence chemotaxis. This paper provides a new component in the chemotaxis pathway of C. jejuni for the first time and highlight the complexity of this remarkable pathway.